Tantangan Peserta Didik SMK dalam Memasuki Perguruan Tinggi dan Peran Pelayanan Konseling - Triave Nuzila Zahri; Yarmis Syukur; Isna Tania (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
This article discusses the challenges of students in continuing their education to higher education, especially students from vocational or vocational high schools. Vocational (vocational) high school students can continue their education to higher education in addition to having great opportunities to enter the world of work. Students who wish to continue their education to tertiary institutions do not show the required preparation. Likewise, students who will choose to work after completing Vocational High School are less mature in entering the world of work. This study aims to analyze the preparation of students in continuing their education to higher education. This type of research is descriptive research. The research subjects were students of vocational high schools, amounting to 89 people. The questionnaire in this research uses the theory developed by Prayitno. The results showed that at least the number of students who made preparations before they entered college. Thus, it is hoped that the counselor can help improve students' understanding of themselves and their environment, in preparation for entering college.